High pot but no T - Manrique-Gonzalez, Luis Miguel (2020)
Introduction. The identification and treatment of patients with hyperkalemia is necessary to prevent the development of arrhythmias. Pseudohyperkalemia is most commonly due to specimen haemolysis and is often recognised by laboratory scientists who subsequently report test results with cautionary warnings. The authors present a case of pseudohyperkalemia in a patient with chronic lymphocytic leukaemia. Report case: the technical factors and method of transport are a potential cause of pseudohyperkalemia. Pseudohyperkalemia has been associated with hyperleukoctosis, in cancer patient populations, more commonly in CLL in adults, but also acute lymphoblastics leukemia in children. This places the patient at risk of unnecessary and potentially dangerous treatments. Conclusion: Physicians should consider pseudohyperkalemia as the underlying cause of elevated potassium levels in patients with malignant leucocytosis who do not have signs or symptom of systemic hyperkalemia.